ANALISIS KINERJA PEKERJA KONSTRUKSI: PERAN WORK-LIFE BALANCE DAN COUNTERPRODUCTIVE WORK BEHAVIOR PADA SALAH SATU PERUSAHAAN KONSTRUKSI DI KABUPATEN GRESIK - Reta Amalia; Dewi Khrisna Sawitri (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Employee performance is an important benchmark for a company to achieve success. A company must pay attention to aspects related to employee performance such as maintaining employee work-life balance and paying attention to employee work behavior. The study aims to determine the direct effect of Work-Life Balance on Employee Performance and the indirect effect of Work-Life Balance on Employee Performance with Counterproductive Work Behavior as a mediating variable. This type of research is quantitative research. The study population was 150 workers and the research sample was 60 workers. The sample determination was carried out using probability sampling techniques and the number of samples was determined based on the Slovin formula. The data analysis technique used the SEM-PLS method. The results of the study concluded that Work-Life Balance has a positive and significant effect on Employee Performance and Work-Life Balance has a positive and significant effect on Employee Performance with the mediating role of Counterproductive Work Behavior.